Pembagian Harta Waris Antara Anak Laki-Laki Dan Anak Perempuan: Studi Putusan Pengadilan Agama Semarang Nomor: 1545/PDT.G/2010/PA.SM - Rochmad Rochmad (Jurnal Hukum Khaira Ummah, 2020)
This research about the distribution of inheritance of girls and boys in practice in religious courts. This type of research is doctrinal/normative law research, with case approach. Based on the research results, it can be seen that the distribution of inheritance between the boys and girls based on the verdict of judges in Pengadilan Agama Semarang, in principle they are the heirs of the boys will get the right of inheritance that is twice the size of the girl's share. The basic consideration of the judge's decision in Pengadilan Agama Semarang in determining the distribution of the inheritance between boys and girls is based solely on the provisions of the law applicable in Islamic law alone, without providing a clear argument and grounds for reasons , why the share of inheritance received by boys is twice as large as girls, so the basis of these considerations has not been able to answer relevant and reconstructive complex issues in the field of inheritance law in the modern era today. Keywords: distribution, inheritance, boys, girls, Religious Courts of Semarang